Психологические особенности деятельности специалистов по информационным технологиям с учетом системного подхода - Фурманец, Борис Иванович; Мовчан, Яна Александровна (НТУ "ХПИ", 2012)
The article describes the system-conceptual approach to the justification of the essence, psychological characteristics and patterns of information technology professionals and their professional activities, taking into account the level of qualification.
Keywords: профессиональная деятельность специалиста; системный подход; психолого-профессиональные требования; конструкции системного подхода